Between clarity and novelty implementation in Indonesia online media according to the principle of journalist - Rizkiansyah, Mariko; Muslikhin,; Wiratma, Margana (Penerbit Universiti Kebangsaan Malaysia, 2020)
The number of online media in Indonesia has been increasing in the last five years. The developments of the number of online mass media are followed by the increasing of share information through social media, including real or fake news. Online mass media activity to keep the balance between actuality and accuracy when they searching and publishing news to the public. This research aims to find how the process of journalist’s works between accuracy and actuality in the online mass media in Indonesia. Another purpose of this research is to find out how the journalist deals with accuracy and actuality according to the element of journalistic principles. The research was conducted by observations and interview on the online mass media managers in Indonesia which are detik.com, kompas.com, suara.com and liputan6.com. The result of the research is online media using elements of journalism to publish their news to keep novelty and clarity. They also convinced that it is hard to implement the element of journalism one hundred per cent because there are so many restrictions, such as the influences of owner interest and policy from company or government. Therefore, profit from user become their main target than create a truth of information based on the element of journalistic principles.